A Two-Step Econometric Estimation of Covariates of Side Selling: The Case of Coffee Cooperatives in Southwest Ethiopia. Issue 10 (3rd October 2018) - Shumeta, Zekarias; D'Haese, Marijke; Verbeke, Wim
Abstract: Despite their apparent economic benefit to smallholder farmers, cooperatives are vulnerable to the problem of side selling. Using cross-sectional household data and Cragg's regression model, we identified the determinants of side selling by coffee cooperative farmers in southwest Ethiopia. The bootstrapping technique was applied to extract average partial effects from the model coefficients. Certified, elder and educated farmers who have off-farm income and trust in the cooperative leadership have been found to side-sell significantly less. Nonetheless, cooperative group size and late payment favoured more side selling. Based on these findings, possible interventions are highlighted for improving cooperative members' commitment and the performance of coffee cooperatives in the region.